PERBEDAAN TINGKAT STRES MAHASISWA PRAKTIK KLINIK PADA TINGKAT II DAN III PROGRAM STUDI D-III KEPERAWATAN STIKES KEPANJEN - Qori Fanani (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2019)
Abstract : Nursing students often experience stress or stress in undergoing clinical practice. There are several factors that cause students to experience stress, including lack of knowledge and skills, workloads and assignments, and the clinical environment itself. The purpose of this study was to determine the differences in stress levels of clinical practice students at level II and level III of Nursing Diploma III Program at STIKes Kepanjen. This type of research is descriptive quantitative with a causal comparative approach with a total of 60 respondents. Data analysis using Mann – Whitney so that the results show that there are significant differences in the level of stress level II and level III students in conducting clinical studies. While for the stressors of students who are undergoing clinical practice are lack of knowledge and skills, workload and assignments, hospital environment and when caring for patients. So that to achieve the goal of clinical learning is to prepare students both knowledge, skills and maturity in dealing with pressure when carrying out clinical learning.Keywords : Clinical practice, Nursing Student